Fusarium agapanthi sp. nov., a novel bikaverin and fusarubin-producing leaf and stem spot pathogen of Agapanthus praecox (African lily) from Australia and Italy. (1st September 2016) - Edwards, Jacqueline; Auer, Desmond; de Alwis, Sri-Kanthi; Summerell, Brett; Aoki, Takayuki; Proctor, Robert H.; Busman, Mark; O'Donnell, Kerry
Abstract : This study was conducted to characterize a novel Fusarium species that caused leaf and stem spot on Agapanthus praecox (Agapanthus, African lily) in northern Italy and leaf rot and spot on the same host in Melbourne, Australia. Formally described as Fusarium agapanthi, this pathogen was analyzed using phenotypic, phytopathogenic, secondary metabolite, molecular phylogenetic and genomic data. Five strains were characterized, including one isolated in 1999 from symptomatic A. praecox in Saluzzo, Italy, and four in 2010 from diseased leaf tissue from the same host exhibiting leaf rot and spot symptoms in the Melbourne Gardens, Royal Botanic Gardens Victoria, Australia. Maximum parsimony and maximum likelihood molecular phylogenetic analyses of portions of six individual genes and the combined dataset all strongly supported F. agapanthi either as the earliest diverging genealogically exclusive lineage in the American Clade of the F. fujikuroi species complex, or alternatively a novel monotypic lineage sister to the American Clade. Koch's postulates were completed on dwarf blue- and large white-flowering varieties of A. praecox, where two isolates of F. agapanthi produced slowly spreading necrotic lesions when inoculated onto leaves and flower stems. Fusarium agapanthi is distinguished from other fusaria by the production of densely branched aerial conidiophores with polyphialides throughout the aerial mycelium on synthetic nutrient-poor agar. BLASTn searches of the F. agapanthi NRRL 31653 and NRRL 54464 (= VPRI 41787) genome sequences were conducted to predict sexual reproductive mode and mycotoxin potential. Results indicated that they possessed MAT1-2 and MAT1-1 idiomorphs, respectively, indicating that this species might be heterothallic. Furthermore, based on the presence of homologs of the bikaverin and fusarubin biosynthetic gene clusters in the F. agapanthi genomes, liquid chromatography-mass spectrometry analysis was conducted and confirmed production of these secondary metabolites in rice and corn kernel cultures of the fungus.